2016
DOI: 10.1007/s00706-016-1866-8
|View full text |Cite
|
Sign up to set email alerts
|

On the origin of the stereoselectivity in chiral amide-based ammonium ylide-mediated epoxidations

Abstract: Detailed DFT studies provide an in-depth mechanistic understanding for the use of chiral amide-based ammonium ylides in epoxidation reactions. It is shown that the used chiral auxiliary efficiently shields one face of the ylide, which thus results in an extraordinarily high stereoselectivity giving only one trans-isomer with perfect control of the absolute configuration.Graphical abstract Electronic supplementary materialThe online version of this article (doi:10.1007/s00706-016-1866-8) contains supplementary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
(25 reference statements)
0
4
0
Order By: Relevance
“…For the ammonium salts 2 , Me 3 N was chosen as the amine component because of its proven superior leaving group ability compared to other achiral tertiary amines. [11b,11d] An initial screening of different solvents and temperatures revealed that the reactions are best carried out in CH 2 Cl 2 at room temperature for 20 h. This was also carefully double-checked with the optimized conditions and it turned out that longer reaction times and/or higher temperatures lead to a pronounced decomposition of the product 1a under the basic conditions. While the use of sodium- and potassium carbonate did not result in any product formation (entries 1 and 2), the use of an excess of K 3 PO 4 lead to the slow formation of a mixture of the three trans , trans , cis -diastereomers (D1, D2, D3) of cyclopropane 1a (entry 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the ammonium salts 2 , Me 3 N was chosen as the amine component because of its proven superior leaving group ability compared to other achiral tertiary amines. [11b,11d] An initial screening of different solvents and temperatures revealed that the reactions are best carried out in CH 2 Cl 2 at room temperature for 20 h. This was also carefully double-checked with the optimized conditions and it turned out that longer reaction times and/or higher temperatures lead to a pronounced decomposition of the product 1a under the basic conditions. While the use of sodium- and potassium carbonate did not result in any product formation (entries 1 and 2), the use of an excess of K 3 PO 4 lead to the slow formation of a mixture of the three trans , trans , cis -diastereomers (D1, D2, D3) of cyclopropane 1a (entry 3).…”
Section: Resultsmentioning
confidence: 99%
“…[10] Our group has a long-standing research focus on (asymmetric) ammonium ylide-mediated cyclization reactions. [11,12] Given the interest in F-containing cyclopropanes, we thus became interested in testing the potential of ammonium and sulfonium ylides to access trifluoroacetyl-containing cyclopropanes 1 . These highly functionalized cyclopropanes have so far only sparingly been investigated,[13] and we therefore rationalized that an addition of carbonyl-stabilized ammonium or sulfonium ylides 2 and 3 to the easily accessible Michael acceptors 4 would result in a powerful method to access a variety of these highly functionalized target molecules (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…In 2015, we developed a chiral amide-based auxiliary approach for this reaction by using simple phenylglycinol-based amide 65 as an ylide precursor. [44] This simple auxiliary (which clearly outperformed other commonly employed amide auxiliaries[44]) allowed us to obtain epoxide 66 in good yields as a single trans diastereomer (Scheme 17 A). We also showed that the auxiliary could be cleaved under reductive conditions to obtain glycidic alcohol 67 .…”
Section: Formal [2+1] Cyclizationsmentioning
confidence: 99%
“…Unfortunately, these reactions are less clean, somewhat lower yielding, and also slightly less selective than the epoxidations. [40, 44]…”
Section: Formal [2+1] Cyclizationsmentioning
confidence: 99%